Longevity of neonicotinoid seed treatments in cotton seedlings under various deficit irrigation levels - Aqeela Sehrish; Suhas Vyavhare; Megha Parajulee; Cade Coldren; Haydee Laza; Catherine Simpson (Scientific Reports)
Abstract Neonicotinoids are one of the most widely used classes of insecticides in agriculture. They are systemic insecticides mainly used as seed treatments to manage sucking insect pests in a wide range of field crops. Environment and growing conditions can impact the efficacy of neonicotinoid seed treatments. To evaluate this, an experiment was conducted to study the interactive effect of soil, water levels on the neonicotinoid concentration and plant growth in cotton. The experiment was laid out in a split-plot design, with three water levels, 30%, 60%, and 100% (control) of recommended irrigation and four seed treatments, including clothianidin, thiamethoxam, imidacloprid and an untreated control. Cotton seedlings were collected and analyzed for physiological changes and neonicotinoid concentrations at 15, 30 and 45 days after germination (DAG). Data were collected on plant height, fresh biomass and leaf area. The neonicotinoid concentrations were analyzed in leaf tissues using LC-MS/MS. The 30% and 60% of recommended irrigation treatments resulted in significantly taller seedlings with greater biomass and leaf area compared to the 100% water saturation (control) treatment. Thiamethoxam-treated seedlings had greater plant height and shoot fresh mass compared to clothianidin and the untreated control, whereas imidacloprid-treated seedlings had greater leaf area than thiamethoxam, clothianidin, and control at all water levels. 30% recommended irrigation increased neonicotinoid concentrations in leaf tissues, with clothianidin showing higher levels compared to other neonicotinoids at 45 DAG. Neonicotinoid seed treatment efficacy may vary with environmental factors, impacting sustainable pest control.